2018
DOI: 10.1111/jdv.15166
|View full text |Cite
|
Sign up to set email alerts
|

Rosacea‐like demodicosis (but not primary demodicosis) and papulopustular rosacea may be two phenotypes of the same disease – a microbioma, therapeutic and diagnostic tools perspective

Abstract: Linked article: This article is commentary on by F. Forton et al., pp. e47–e48 in this issue. To view this article visit https://doi.org/10.1111/jdv.15162

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
2
24
1
Order By: Relevance
“…It is common knowledge that hospitals are threatened by nosocomial infections due to these killer microorganisms [11]. The adverse effects of different synthetic drugs are wellknown when they are prescribed for different diseases or comorbidities [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].The usage of natural extracts or plant derivates is desirable for their efficacy without major adverse reactions even on normal microbioma, or if needed after the informed consent even in pregnancy [30][31][32][33][34][35][36][37][38][39][40][41][42].It is possible to use these natural products under various pharmaceutical forms, some of them even retard forms, in view of reducing nosocomial infections in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…It is common knowledge that hospitals are threatened by nosocomial infections due to these killer microorganisms [11]. The adverse effects of different synthetic drugs are wellknown when they are prescribed for different diseases or comorbidities [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].The usage of natural extracts or plant derivates is desirable for their efficacy without major adverse reactions even on normal microbioma, or if needed after the informed consent even in pregnancy [30][31][32][33][34][35][36][37][38][39][40][41][42].It is possible to use these natural products under various pharmaceutical forms, some of them even retard forms, in view of reducing nosocomial infections in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Rosacea and demodicosis are common dermatoses, but classification and diagnostic criteria are still controversial . The National Rosacea Society expert committee defines rosacea as a central‐face distribution of at least one of four primary features: flushing, persistent erythema, papules and pustules, and telangiectasia.…”
mentioning
confidence: 99%
“…Rosacea and demodicosis are common dermatoses, but classification and diagnostic criteria are still controversial. [1][2][3][4][5][6][7] The National Rosacea Society expert committee defines rosacea as a central-face distribution of at least one of four primary features: flushing, persistent erythema, papules and pustules, and telangiectasia. The committee identified four subtypes: erythematotelangiectatic rosacea (ETR), papulopustular rosacea (PPR), phymatous rosacea and ocular rosacea.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of atopic dermatitis, studies have suggested a decrease in the normal flora, which can correlate with acute stages of the disease. A study has emphasized that after anti-inflammatory and emollients treatments normal genus like Streptococcus, Propionibacterium and Corynebacterium increased in the skin [23][24][25][26][27][28][29][30]. We should be aware of the cutaneous side effects of topical steroids even on skin normal microbioma [31][32][33].…”
Section: Does Treatment Affect the Cutaneous Microbiome?mentioning
confidence: 99%